Bloodletting Puncture at Hand Twelve Jing-Well Points Improves Neurological Recovery by Ameliorating Acute Traumatic Brain Injury-Induced Coagulopathy in Mice - Li, Bo; Zhou, Xiu; Yi, Tai-Long; Xu, Zhong-Wei; Peng, Ding-Wei; Guo, Yi; Guo, Yong-Ming; Cao, Yu-Lin; Zhu, Lei; Zhang, Sai; Cheng, Shi-Xiang (Frontiers in Neuroscience, 2020)
Traumatic brain injury (TBI) contributes to hypocoagulopathy associated with prolonged bleeding and hemorrhagic progression. Bloodletting puncture therapy at hand twelve Jing-well points (BL-HTWP) have been applied as a first aid measure in various of emergent neurological diseases, but the detailed mechanisms of the modulation between the central nervous system and systemic circulation after acute TBI in rodents remain unclear. To investigate whether BL-HTWP stimulation modulates hypocoagulable state and exerts neuroprotective effect, experimental TBI model of mice was produced by the controlled cortical impactor (CCI) and treated BL-HTWP were immediately made after CCI. Then, the effects of BL-HTWP on the neurological function, cerebral perfusion state, coagulable state, and cerebrovascular histopathology post-acute TBI were determined, respectively. Results showed that BL-HTWP treatment attenuated cerebral hypoperfusion and improve neurological recovery post-acute TBI. Furthermore, BL-HTWP stimulation reversed acute TBI-induced hypocoagulable state, reduced vasogenic edema and cytotoxic edema by regulating multiple hallmarks of coagulopathy in TBI. Therefore, we conclude for the first time that hypocoagulopathic state occurs after acute experimental TBI and the neuroprotective effect of BL-HTWP relies on, at least in part, the modulation of hypocoagulable state. BL-HTWP therapy may be a promising strategy for acute severe TBI in the future.